2009
DOI: 10.1007/s12665-009-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

O, H, and Sr isotope evidences of mixing processes in two geothermal fluid reservoirs at Yangbajing, Tibet, China

Abstract: The Yangbajing geothermal field with the highest reservoir temperature among Chinese hydrothermal systems is located about 90 km northwest to Lhasa City, capital of Tibet, where high temperature geothermal fluids occur in two reservoirs: a shallow one at a depth of 180-280 m and a deep one at 950-1,850 m. In this study, Oxygen-18 and deuterium isotope compositions as well as 87 Sr/ 86 Sr ratios of water samples collected from geothermal wells, cold springs and surface water bodies were characterized to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Based on this, we consider that with the continuous advancement of extraction technologies, geothermal-type lithium resources have the potential to become a new genetic type of lithium ore deposit. This article absorbs and summarizes previous relevant research materials (Zheng and Liu, 1982, 1987Zheng et al, 1983Zheng et al, , 1989Zheng et al, , 1990Zheng et al, , 1995Tong et al, 1981Tong et al, , 2000Zheng S H et al, 1982;Duo, 2003;Luo et al, 2017;Guo and Wang, 2012;Pang et al, 2013;Tan et al, 2014Tan et al, , 2018Zheng W et al, 2015;Wang R C, et al, 2017;Mao, 2018;Guo et al, 2007Guo et al, , 2009Guo et al, , 2010Guo et al, , 2012Guo et al, , 2017Guo et al, , 2019aGuo et al, , 2019bXia and Zhang, 2019;Zhang et al, 2019). Together with field investigations and research on the key areas in southern Xizang (e.g., the Gudui geothermal field), we aim to report the characteristics, distribution and scale, origin and utilization prospects of geothermal-type lithium resources in southern Xizang.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Based on this, we consider that with the continuous advancement of extraction technologies, geothermal-type lithium resources have the potential to become a new genetic type of lithium ore deposit. This article absorbs and summarizes previous relevant research materials (Zheng and Liu, 1982, 1987Zheng et al, 1983Zheng et al, , 1989Zheng et al, , 1990Zheng et al, , 1995Tong et al, 1981Tong et al, , 2000Zheng S H et al, 1982;Duo, 2003;Luo et al, 2017;Guo and Wang, 2012;Pang et al, 2013;Tan et al, 2014Tan et al, , 2018Zheng W et al, 2015;Wang R C, et al, 2017;Mao, 2018;Guo et al, 2007Guo et al, , 2009Guo et al, , 2010Guo et al, , 2012Guo et al, , 2017Guo et al, , 2019aGuo et al, , 2019bXia and Zhang, 2019;Zhang et al, 2019). Together with field investigations and research on the key areas in southern Xizang (e.g., the Gudui geothermal field), we aim to report the characteristics, distribution and scale, origin and utilization prospects of geothermal-type lithium resources in southern Xizang.…”
mentioning
confidence: 84%
“…Yangbajain is chosen because, among all the hydrothermal areas in Tibet, it has been investigated systematically in the past three decades (Tong et al, 1981;Zhao et al, 1998b;Duo, 2003;Guo et al, 2007Guo et al, , 2009, and the existence of a magmatic heat source and high-temperature reservoir (over 200°C) has also been confirmed (Guo et al, 2014). Guo et al (2010) showed that the deep geothermal fluid is the mixing product of both magmatic and infiltrating snow -melt water, whereas the shallow geothermal fluid is formed by the mixing of deep geothermal fluid with cold groundwater (mixing process and ratios are shown in the Fig. 4).…”
Section: Origin Of High-temperature Li-rich Geothermal Resources In Southern Xizangmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be caused by the interaction of the circulating hot springs with the evaporitic (CaSO 4 ) units, which is confirmed by the wide distribution of Paleogene evaporite strata in the Qamdo Basin. While Ca 2+ and Mg 2+ in geothermal waters from Yangbajing and western Yunnan are less relevant to the evaporite or the carbonatite, they may have something to do with the large granitic batholiths and metamorphic reservoir host rocks [34,71]. The Ca + Mg is enriched relative to HCO 3 and depleted relative to Clin saline springs from the study area and in the Lanping-Simao Basin, indicating that the dissolution of evaporites (halite, sylvine, and gypsum/anhydrite) is the principal sources of solutes for the saline springs.…”
Section: Solute Sources and Genesis Of Spring Watersmentioning
confidence: 99%
“…Mixing is a common process during the upward flow of geothermal water. Geothermal waters might be a mixture of magmatic water, stream, deep geothermal fluids, shallow geothermal fluids, and cold water from the surface [13,[15][16][17][18][19]. Mixing is also a process that controls outlet temperatures and causes dilution of geothermal water [5].…”
Section: Introductionmentioning
confidence: 99%